2001
DOI: 10.1074/jbc.m101084200
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone-related Peptide Stimulates Osteogenic Cell Proliferation through Protein Kinase C Activation of the Ras/Mitogen-activated Protein Kinase Signaling Pathway

Abstract: We investigated the mechanisms of parathyroid hormone-related peptide (PTHrP)-mediated effects on osteogenic cells in primary rat bone marrow cell (BMC) cultures. We first demonstrated by reverse transcriptase-polymerase chain reaction and immunocytochemistry that BMCs express the type I parathyroid hormone/PTHrP receptor. Treatment with PTHrP increased osteogenic cell proliferation as determined by [ 3 H]thymidine and bromodeoxyuridine incorporation and augmented osteogenic colonies. Immunocytochemistry and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 56 publications
2
60
1
1
Order By: Relevance
“…In contrast to the in vivo and in vitro evidence for a direct anti-mitotic action of short term exposure of osteoblast progenitors to PTH, osteogenic cell replication was stimulated by 6 hours of exposure to PTH or PTHrP in cultures established from the bone marrow [69] or calvaria [70] of young rats. In addition, treatment of embryonic chick periosteal cells with PTH for 5-30 minutes stimulated proliferation [71].…”
Section: Effects Of Intermittent Pth On the Replication And Differentmentioning
confidence: 60%
“…In contrast to the in vivo and in vitro evidence for a direct anti-mitotic action of short term exposure of osteoblast progenitors to PTH, osteogenic cell replication was stimulated by 6 hours of exposure to PTH or PTHrP in cultures established from the bone marrow [69] or calvaria [70] of young rats. In addition, treatment of embryonic chick periosteal cells with PTH for 5-30 minutes stimulated proliferation [71].…”
Section: Effects Of Intermittent Pth On the Replication And Differentmentioning
confidence: 60%
“…To begin to explore the intracellular mechanisms that might mediate these effects, we elected to characterise the signalling pathways that mediate the proliferative actions of PTHRP in MCF-7 cells. The PTHRP-R can couple to multiple signalling systems, including Ca 2+ /protein kinase C, cAMP and Ras/ERK pathways (Carpio et al, 2001;Miao et al, 2001). PTHRP did not induce Ca 2+ accumulation in MCF-7 cells (data not shown) in agreement with a previous report (Birch et al, 1995), making it unlikely that this pathway contributes to the mitogenic actions of PTHRP.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our results, the MAPK pathway was reported to mediate parathyroid hormone-related peptide stimulation of type I collagen gene expression and alkaline phosphatase activity in MG-63 cells (8). Swarthout et al (9) also recently showed that low concentrations of PTH (10 Ϫ12 to 10 Ϫ11 M) can substantially increase MAPK activity in UMR-106-01 and primary rat osteoblasts (52).…”
Section: Fig 5 Effect Of Pth Treatment On the Binding Of Nuclear Exmentioning
confidence: 99%